Meningkatkan Kemampuan Penalaran Matematis dengan Penerapan Pendekatan Bridging Analogy Ditinjau dari Self-Efficacy - Nia Agustiana; Nanang Supriadi; Komarudin Komarudin (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
The purpose of this study was to find out the teaching and learning activities using the bridging analogy method and see the improvement of students 'mathematical reasoning abilities through the treatment of bridging analogy approach and see the differences in the increase in mathematical reasoning abilities in terms of students' self-efficacy. The research method used is the experimental method. The method of data collection in this study is questionnaires and tests. The sample used was class VIII students of SMP 19 Pesawaran. Based on the results of the study there is an increase in students' mathematical reasoning abilities using a bridging analogy approach. The marginal average in the analogy bridging approach is 0,73, which means it has a high N-Gain interpretation. The results also obtained a difference in the increase in students' mathematical reasoning abilities in terms of self-efficacy. Increased mathematical reasoning ability of high self-efficacy students is better than moderate and low self-efficacy but moderate and low self-efficacy does not have a significant difference.